Culture and profitability: empirical evidence at a European level - Martins, M. M.; Lopes, I. T. (Corporate Ownership And Control, 2016)
Organizational cultures distinguish different organizations within the same country or countries. When comparing the organizations within the same country differences in national cultures are not relevant but become relevant in comparison between different countries. This paper intends to evidence whether the profitability of companies can be influenced by the national culture. In order to characterize the culture of each country, we used the Hofstede measure of cultural dimensions (1. Power Distance (PDI); 2. Uncertainty Avoidance (UAI); 3. Individualism (IDV); 4. Masculinity (MAS); 5. Long-Term Orientation (LTO); and 6. Indulgence vs Restraint (IND)). Sample was based on the 500 largest European companies rated by the Financial Times 2015. Profitability was measured by the ratios Return on Assets (ROA) and Return on Equity (ROE). Statistical tests were performed to test whether the means of the variables used to measure profitability are statistically equal. The results indicate that companies with higher profitability are from countries with lower Power Distance, lower Uncertainty Avoidance, Long-Term Orientation, and Higher Indulgence.